Improving Bond Strength And Thermal Behaviour Of New Sodalite Infiltrate Ceramic Core Materials - Hamid Naji, Ghassan Abdul-; Omar, Ros Anita; Yahya, Rosiyah (IIUM Medical Journal Malaysia, 2017)
Introduction: The mismatch in coefficient of thermal expansion (CTE) between the veneered porcelain and the ceramic core has been primarily identified as the cause of core/veneer chipping in all-ceramic restorations. This study aimed to evaluate the effect of sodalite infiltration on the CTE behaviour and bond strength of different all-ceramic prostheses. Materials and Methods: The experimental groups were synthesised sodalite-infiltrated alumina (IA-SOD) and synthesised sodalite-infiltrated zirconia-toughened alumina (ZTA) (IZ-SOD), while the control groups were glassinfiltrated alumina (IA-glass) and glass-infiltrated ZTA (IZ-glass). Forty cylindrical-shaped samples (5mm diameter; 10mm height) were tested for CTE. Another forty disc-shaped samples (12mm diameter; 1.2±0.2mm thick) and veneered with cylinder-shaped low-fusing porcelain (2mm high; 2mm diameter) were prepared for shear bond strength test. SEM, stereo microscope and AFM were used to investigate the structural characteristics of samples at the fracture surface. Results: The CTE values for both IZ-SOD and IA-SOD were 8.62 x 10-6 K-1 and 8.37 x 10-6 K-1 respectively, which were statistically higher than IZ-glass and IA-glass (8.08 x 10-6 K-1 and 7.63 x 10-6 K-1 , respectively) (p0.05). Conclusion(s): The higher CTE mismatch and bond strength of the newly developed SOD-infiltrated samples than did the commercial glassinfiltrated samples could thus make them suitable for all-ceramic dental prostheses.